Broadway, Port of Spain - Briant (My University, 2010)
Tram lines leading to tram station, located near Broadway in Port of Spain. Today the area where the station was located is called City Gate.
Colour: Sepia; Style: Landscape; Other: Bordered, Divided
Keywords: Trinidad and Tobago; Postcards; Cities and towns--Trinidad and Tobago--Port of Spain; Broadway; Street-railroad tracks--Trinidad and Tobago; Architecture--Trinidad and Tobago